Use of Augmented Reality for Computational Thinking Stimulation through Virtual Toys - Esteves, Adson; Santana, André; Lyra, Rodrigo (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2019: Anais do XXI Simpósio de Realidade Virtual e Aumentada, 2019)
Studies with augmented reality show that while the technology helps the student learn, it may end up disturbing other points, showing that more research is needed with the use of augmented reality. Also, a topic that is growing within education is Computational Thinking, which says that the thinking like computer scientists is necessary for the 21st century and should be disseminated mainly in schools during basic education. In the face of this, this work created an augmented reality android application that tracks physical tiles and creates 3D maps for the user, also giving a character that can be programmed to walk on this created map, simulating a programming toy. Finally, tests carried out with the application have shown that augmented reality currently has performance problems when multiple targets are used, so, devices with low processing have problems at map tracking. These issues affected the tests with the children, which made it difficult for them to track the map like they wanted, but they still liked the app even after it. That shows that the acceptance of the technology by the children is good, which can help developing Computational Thinking, but the technology limitation is still a problem. These obstacles while currently hindering the use of augmented reality in education may in the future be irrelevant due to the constant advancement of technology. This paper’s main contribution is showing one possibility of using AR with Computational Thinking and what needs to evolve for it to be used by the usable by the children.